Sonochemical synthesis of MnFe2O4 nanoparticles and their electrochemical and photocatalytic properties. (January 2021) - Amulya, M.A. Shilpa; Nagaswarupa, H.P.; Kumar, M.R. Anil; Ravikumar, C.R.; Kusuma, K.B.
Abstract: In this study, the electrochemical characteristics of manganese ferrite (MnFe2 O4 ) nanoparticles were assessed using various electrochemical techniques, including cyclic voltammetry (CV), galvanostatic charge–discharge analysis, and electrochemical impedance spectroscopy. The electrode material comprising MnFe2 O4 nanoparticles with a nanorod spinel structure was synthesized via the sonochemical route and the dimensions in of the nanoparticles ranged from 16 to 24 nm. X-ray diffraction, Fourier transform-infrared spectroscopy, Raman spectroscopy, scanning electron microscopy, energy dispersive X-ray spectroscopy, transmission electron microscopy, and diffuse reflectance spectroscopy were used to determine the characteristics of the MnFe2 O4 nanoparticles. HCl and NaOH were used as electrolytes to study the electrochemical behavior of the nanoparticles. The specific capacitance values determined from the CV curves obtained using the MnFe2 O4 versus Ag/AgCl electrodes at an AC amplitude of 5 mV and in the frequency range from 1 Hz to 1 MHz in acidic and basic electrolytes with concentrations of 0.1 M were 4.2566 F g −1 and 2.2099 F g −1, respectively. The application of MnFe2 O4 as a photocatalyst under ultraviolet light degraded the dyes comprising methylene blue and Drimaren yellow by up to 96% and 7%, respectively. The results obtained in this study verified the potential applications of sonochemically synthesized MnFe2 O4 in semiconductors, sensors, and energy storage devices. Highlights: MnFe2 O4 nanoparticles synthesized using sonochemical method. Electrochemical properties of MnFe2 O4 nanoparticles examined. MnFe2 O4 nanoparticles have possible sensor and supercapacitor applications. MnFe2 O4 acted as photocatalyst to degrade dyes under ultraviolet light.